Perceptions of Turkish Academicians about Predatory Journals: A Qualitative Descriptive Study - Gülçin Mutlu (Anı Publishing, 2020)
Over the recent years, there has been a drastic increase in the number of predatory journals exploiting the norms of publishing ethics under the disguise of open access publishing. In this essence, there is a need to examine the degree to which researchers are aware of such journals to protect science ethics and science communication. To this end, this study aims to describe Turkish academicians' understandings of predatory journals and identify their reasons to publish in them. The results from this basic qualitative descriptive study indicated that Turkish academicians had a certain degree of awareness about these journals, and the characteristics they mentioned align with the literature. Given the reasons of academicians to publish in these journals, the results revealed that Turkish academicians strongly felt the "publish or perish" pressure and had a tendency to publish in these journals to meet the criteria for academic incentives and associate professorship applications.